Mengukur Kinerja Keuangan pada PT Aneka Gas Industri Menggunakan Analisis Laporan Keuangan - Rafly Hasanuddin; Muhammad Zaky Athari Ihsan; Irwan Pratama; Reynaldo Tandean; Hariany Idris (Bata Ilyas Journal of Accounting, 2023)
To choose the monetary presentation of PT. Aneka Gas Industri Tbk utilizes the proportion of liquidity, the proportion of dissolvability and the proportion of productivity for the period 2020- 2021 which is the reason for this test. The exploration configuration used in this test is to explain quantitatively, especially the data obtained from the exploration test population and dissected with a measurable strategy used and afterward described. From the conversation above, it very well may be presumed that PT. Aneka Gas Industri Tbk organization requires an investigation of the proportions, for instance, the proportion of liquidity, the proportion of solvency and the proportion of profitability in order to give an idea of the associations capacity to pay commitments, the capacity to pay the commitments ensured by the guaranteed resources and the capacity to acquire benefits. In light of the assessed extent of liquidity, one might say that the money claimed by PT. Aneka Gas Industri Tbk doesnt yet have the choice to pay its brief commitments. From the estimation results using the solvency proportion, one might say that the organization can pay the obligations guaranteed by its resources. The consequence of calculating the proportion of productivity might say that can be said that the organization must choose between limited options to create a gain. From the assessment results, it will in general be associated that the financial execution with PT. Aneka Gas Industri Tbk doesnt suggest that the association doesnt have the choice to deal with its assets appropriately. This should be visible from the decreasing proportion of liquidity, the increasing proportion of solubility, and the decreasing proportion of productivity.